2013
DOI: 10.9790/0853-0810105
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dermatoglyphic Fingertip Patterns in the prediction of Maturity Onset Diabetes Mellitus (Type II)

Abstract: Dermatoglyphic features are inherited by polygenic system with individual gene contributing a small additive effect. The present research aims to primarily study the various dermatoglyphic patterns in the patients of the Maturity Onset Diabetes Mellitus (Type II diabetes) and compare these statistically with the dermatoglyphic patterns in individuals not suffering from it. The present study was carried out on 101 (51 male and 50 female) clinically diagnosed patients of maturity onset diabetes mellitus. Healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 2 publications
1
19
1
Order By: Relevance
“…It was also noted that there was an increase in the frequency of ulnar loops in both males and females of the diabetic group however; the difference was not statistically significant [2] . In another study by Eberechi et al conductetd in Nigeria, Africa, it was observed that the diabetic subjects had significantly higher frequency of ulnar loops.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It was also noted that there was an increase in the frequency of ulnar loops in both males and females of the diabetic group however; the difference was not statistically significant [2] . In another study by Eberechi et al conductetd in Nigeria, Africa, it was observed that the diabetic subjects had significantly higher frequency of ulnar loops.…”
Section: Discussionmentioning
confidence: 96%
“…They may be affected by environmental and genetic factors in utero [1] . They are also called as the "poor man"s karyotype" since they represent the genetic makeup of an individual.Epidermal ridge patterns show significant findings in patients of diseases with a strong or partial genetic background [2] . A very well-known example of dermatoglyphic finding is the presence of Simian crease in patients of Down"s syndrome which has a strong genetic background.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They signify 'dat' edges were essentially thin just in the left hand of diabetic females when contrasted with left hands of female controls. Burute et al (2013) have meant to contemplate the different dermatoglyphic patterns in the patients of the development beginning diabetes mellitus (Type 2 diabetes mellitus) and contrasted and the dermatoglyphic patterns of controls. They did their investigation on 101 (51 male and 50 female) clinically analyzed patients of development beginning diabetes mellitus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They can be used as diagnostic aid in the screening of genetically inherited diseases [11]. In congenital diseases, significant dermatoglyphic patterns are useful in identifying Down syndrome (mongolism) in babies [9].…”
Section: Role Of Dermatoglyphicsmentioning
confidence: 99%